Psikologi Kepemimpinan - Hanumatul Hasuna Soraya; Khuriatus Salamah; Fahmi Ulum; Mu’alimin Mu’alimin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
A leader who has a good leadership spirit will be able to maximize his performance so that the desired goals can be realized. Leadership from a psychological perspective discusses the leader's personality. This research aims to reveal the leader's personality based on a psychological perspective including the leadership model applied that influences success in leading. Leadership style influences how the leader is viewed or respected by the individuals being led. It is hoped that the results of this literature review can be used as research or information that can be used as a theoretical basis for further research in leadership based on psychological aspects.